Cytoplasmic vacuolation with endoplasmic reticulum stress directs sorafenib induced non-apoptotic cell death in hepatic stellate cells - Sachin Sharma (Nature Portfolio, 2021)
Abstract The activated hepatic stellate cells (HSCs) are the major cells that secrete the ECM proteins and drive the pathogenesis of fibrosis in chronic liver disease. Targeting of HSCs by modulating their activation and proliferation has emerged as a promising approach in the development of anti-fibrotic therapy. Sorafenib, a multi-kinase inhibitor has shown anti-fibrotic properties by inhibiting the survival and proliferation of HSCs. In present study we investigated sorafenib induced cytoplasmic vacuolation mediated decreased cell viability of HSCs in dose and time dependent manner. In this circumstance, sorafenib induces ROS and ER stress in HSCs without involvement of autophagic signals. The protein synthesis inhibitor cycloheximide treatment significantly decreased the sorafenib-induced cytoplasmic vacuolation with increasing cell viability. Antioxidant human serum albumin influences the viability of HSCs by reducing sorafenib induced vacuolation and cell death. However, neither caspase inhibitor Z-VAD-FMK nor autophagy inhibitor chloroquine could rescue the HSCs from sorafenib-induced cytoplasmic vacuolation and cell death. Using TEM and ER organelle tracker, we conclude that the cytoplasmic vacuoles are due to ER dilation. Sorafenib treatment induces calreticulin and GPR78, and activates IRE1α-XBP1s axis of UPR pathway, which eventually trigger the non-apoptotic cell death in HSCs. This study provides a notable mechanistic insight into the ER stress directed non-apoptotic cell death with future directions for the development of efficient anti-fibrotic therapeutic strategies.